Analysis of thrombophilic gene mutations in coronary artery ectasia - Zafer Yalım; Serap Tutgun Onrat; Sadık Volkan Emren; İbrahim Etem Dural; Alaettin Avşar; Ersel Onrat (KARE Publishing, 2020)
Objective: Coronary artery ectasia (CAE) is defined as localized or diffuse dilatation in the coronary artery lumen of at least 1.5 times the diameter of adjacent healthy reference segments. The etiology of CAE is still unknown, but the most likely cause is atherosclerosis. The aim of this study was to evaluate several gene polymorphisms that are thought to have an effect on the development of coronary atherosclerosis and have been shown to cause thrombophilia in CAE patients. Methods: The factor V Leiden (G1691A), factor V H1299R, prothrombin G20210A, factor XIII V34L, beta-fibrinogen-455 G>A, plasminogen activator inhibitor (PAI)-1 4G/5G, and methylenetetrahydrofolate reductase (MTHFR) C677T, and MTHFR A1298C polymorphisms were evaluated in 66 patients with CAE and 32 individuals with normal coronary arteries. Results: Comparison of the CAE and control groups revealed that the clinical features and the frequency of polymorphism in the thrombophilic genes were similar in both groups. However, when heterozygous and/or homozygous polymorphism was compared between groups, it was found that there was a significantly higher finding of thrombophilic gene polymorphism in the CAE group (p=0.023). Conclusion: Thrombophilic gene polymorphism may be associated with the formation and clinical presentation of CAE.